Descrição e classificação de predicados nominais com o verbo-suporte fazer no Português do Brasil - Barros, Cláudia Dias de (2014)
Lexical data base building can be considered an essential task for Natural Language Processing (NLP), since the data included can be used in numerous tools, such as Parsers, Semantic Role Labelers, automatic translators, Text Simplifiers, Paraphrases Systems, Question-Answer Systems, Information Extraction Systems, among others. One kind of lexical information that can be used by these systems and, therefore, must be described and formalized is the nominal predicates, which can be defined by the union of a predicative noun and a support verb. Predicative nouns are those with arguments, and support verbs are the ones semantically empty. The latter provides to nouns the tense-aspect-person-number marks that they don t have, given their morphology. In this context, this research presents the linguistic description of 1,815 Brazilian Portuguese nominal predicates (support verb fazer and a predicative noun) according to the Lexicon-Grammar Theory. Such theory proposes that the linguistic unity of analysis is the simple clause (the predicator and its arguments). The data is inserted in a binary table, which presents the lexical entries in rows and the formal properties (structural, distributional and transformational) in columns.Twenty-nine properties were identified, such as (i) the type of prepositions; (ii) the possibility of passive voice, and others. The nominal predicates analysed were divided into 17 classes, which have syntactic regularities. This research has identified the variants of support verb fazer (make/do), in order to expand the possibilities of the ocurrence of these kinds of predicates. This research aims to contribute to the linguistic description of the Brazilian Portuguese language and NLP, providing data to be used in the future by systems that process lexicon.